E-portfolio as an assessment tool in early childhood education (Research, Society and Development, 2023)
The evaluation of the quality of early childhood education is a matter of interest in Brazilian educational policies. The contextual indicators for the evaluation of school units by educational agents are combined with dynamic instruments for the assessment of learning to capture the movement of children's manifestations and expressions at school. The present investigation, of a qualitative nature, aimed to build a collective e-portfolio in early childhood education and reflect on these productions from the perspective of children, their teachers and parents. The data collection instruments were: the e-portfolio, an open questionnaire to 7 families and an interview with 5 teachers and 25 children from a school in the city of São Paulo. The results indicate that 40% of the families were engaged and that the e-portfolio represents for them an extension of their children's learning at home. Teachers pointed out advantages in the reflection that they were able to trigger with the group and the interview with the children revealed expressions such as "I loved it!", "I still didn't know how to write in this task and now I know!". We understand that the e-portfolio demands time, organization and knowledge of digital pedagogical alternatives. It is not always easy to involve families, but the results of observations from the children's universe and the possibilities of interactions in the digital scenario compensate for further studies in the area.